ICU-BPJS Patients’ Satisfaction on Administration Services and Fasilities of Type A Hospital in Jakarta - Rianti Setiadi; Franky Franky (AIBPM Publisher, 2019)
BPJS is a type of insurance that helps the community, especially the poor. Nonetheless, complaints from patients participating in the BPJS often arise, especially towards administrative services and hospital facilities. These complaints need to be considered especially for complaints that come from patients who need intensive care. Each hospital has different administrative services and facilities. In this research, hospital that provides the highest satisfaction for ICU patients who are participating in BPJS, on administrative services and facilities among eight type A hospitals in Jakarta will be searched. The hospital that are included in this research are Hospital B, C, F, G, H, P, S and T. The hospital found can be used as an example for other hospitals. Therefore ICU-BPJS patient complaints can be reduced. Respondents from this study consist of 124 families of ICU-BPJS patients who were treated at the eight hospitals above, taken by purposive sampling method during October to December 2018. Data analysis methods used are the Kruskall Wallis and Least Significant Difference (LSD) methods. The findings of this study are: hospital S has the highest level of satisfaction on facilities for ICU-BPJS patients. The satisfaction on administration between the eight-hospital included in this research is the same.